Quantum Mechanical Predictions of the Antioxidant Capability of Moracin C Isomers - Parise, Angela; De Simone, Bruna Clara; Marino, Tiziana; Toscano, Marirosa; Russo, Nino (Frontiers in Chemistry, 2021)
Antioxidant capability of moracin C and iso-moracin C isomers against the OOH free radical was studied by using density functional theory by using the M06-2X exchange-correlation functional coupled with the all electron 6-311++G(d,p) basis set. Different reaction mechanisms (HAT, SET, RAF ) were taken into account considering water- and lipid-like environments. Rate constants were obtained employing the conventional transition state theory. Results show as in water solvent, for both the isomers, the scavenging activity mainly occurs throughout a radical addition mechanism, while in lipid-like environment the radical addition process is favored for iso-moracin C while both redox and non-redox type reactions can equally occurs for moracin C. For the study in water solvent the relative pKa’s and the deprotonation paths at physiological pH were predicted